InP Quantum Dots: Synthesis and Lighting Applications - Chen, Bing; Li, Dongyu; Wang, Feng (Small (Weinheim an der Bergstrasse, Germany), 2020)
InP quantum dots (QDs) are typical III–V group semiconductor nanocrystals that feature large excitonic Bohr radius and high carrier mobility. The merits of InP QDs include large absorption coefficient, broad color tunability, and low toxicity, which render them promising alternatives to classic Cd/Pb‐based QDs for applications in practical settings. Over the past two decades, the advances in wet‐chemistry methods have enabled the synthesis of small‐sized colloidal InP QDs with the assistance of organic ligands. By proper selection of synthetic protocols and precursor materials coupled with surface passivation, the QYs of InP QDs are pushed to near unity with modest color purity. The state‐of‐the‐art InP QDs with appealing optical and electronic properties have excelled in many applications with the potential for commercialization. This work focuses on the recent development of wet‐chemistry protocols and various precursor materials for the synthesis and surface modification of InP QDs. Current methods for constructing light‐emitting diodes using novel InP‐based QDs are also summarized. InP nanocrystals are promising alternatives to classic Cd/Pb‐based quantum dots (QDs) for applications in practical settings owing to the low toxicity and high emission efficiency. This work focuses on the recent advances in the synthesis and surface modification of InP QDs as well as their applications in light‐emitting diodes.